1985
DOI: 10.1017/s1742758400004549
|View full text |Cite
|
Sign up to set email alerts
|

Biotypes of the brown planthopper Nilaparvata lugens (Stål) and strategies in deployment of host plant resistance

Abstract: Resistant rice varieties have proved to be highly effective against the brown planthopper Nilaparvata lugens (Stal), but their long-term stability is threatened because of the evolution of prolific biotypes. At present, identification of biotypes is based principally on the differential reactions of host rice varieties to pest in greenhouse screenings and in field plantings of test nurseries at many locations. So far, three N. lugens biotypes that attack different rice varieties have been identified in the Phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…This result corroborates the findings of Tan et al (1995), Latif et al (2008), and Claridge et al (1985a, b). Saxena and Barrion (1985) also reported that karyotypes, idiograms, nuclear organelles, and chromosomes within the nucleolus-organizing region (site of RNA synthesis) showed clear differences between rice-and Leersiainfesting populations of N. lugens. Despite their morphological similarities, a distinct cytological incongruity and a certain degree of genetic isolation between the two populations was inferred.…”
Section: Discussionmentioning
confidence: 92%
“…This result corroborates the findings of Tan et al (1995), Latif et al (2008), and Claridge et al (1985a, b). Saxena and Barrion (1985) also reported that karyotypes, idiograms, nuclear organelles, and chromosomes within the nucleolus-organizing region (site of RNA synthesis) showed clear differences between rice-and Leersiainfesting populations of N. lugens. Despite their morphological similarities, a distinct cytological incongruity and a certain degree of genetic isolation between the two populations was inferred.…”
Section: Discussionmentioning
confidence: 92%
“…host-mediated behavioral and physiological responses, morphological differences, cytological behavior, and crossability differences (Saxena and Barrion, 1985). Accumulation of host-adapted gene complexes in the pest may have led to differentiation of populations on rice varieties with genes for resistance and on the nonrice host, L. hexandra.…”
Section: !I~iimentioning
confidence: 99%
“…Differentiation of the two species may have resulted from single-gene substitutions or chromosomal rearrangements, provided that these changes act to interrupt the gene flow between populations (Bush, 1975). Similar genetic events may have led to the evolution of N. lugens biotypes which were observed to have considerable differences in cytological behavior and crossability (Saxena and Barrion, 1985). In another study, we have analyzed the allozyme variation ofN.…”
Section: !I~iimentioning
confidence: 99%
See 2 more Smart Citations